2014
DOI: 10.1186/s12964-014-0050-1
|View full text |Cite
|
Sign up to set email alerts
|

TCR-triggered extracellular superoxide production is not required for T-cell activation

Abstract: BackgroundIn the last decade, reactive oxygen species (ROS) production has been shown to occur upon T-cell receptor (TCR) stimulation and to affect TCR-mediated signalling. However, the exact reactive species that are produced, how ROS are generated and their requirement for T-cell activation, proliferation or cytokine production remain unclear, especially in the case of primary human T cells. Moreover, several groups have questioned that ROS are produced upon TCR stimulation.ResultsTo shed some light onto thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 32 publications
0
16
0
Order By: Relevance
“…Additionally, in non-single cell studies the generation of ROS from contaminating phagocytes present in T-cell preparations isolated from lymphoid tissues may lead to artifacts. In fact, we have found a significant release of O 2 ·-upon stimulation of T-cell suspensions (whose purity more than 96%) with isotype controls (Belikov et al, 2014). It is believed that this non-TCR-mediated O 2 ·-originates upon stimulation of Fc receptors on monocytes contaminating purified T-cell suspensions Belikov et al, 2014).…”
Section: The Ws Of Ros Production In T Cells: When Where What and Whymentioning
confidence: 79%
See 4 more Smart Citations
“…Additionally, in non-single cell studies the generation of ROS from contaminating phagocytes present in T-cell preparations isolated from lymphoid tissues may lead to artifacts. In fact, we have found a significant release of O 2 ·-upon stimulation of T-cell suspensions (whose purity more than 96%) with isotype controls (Belikov et al, 2014). It is believed that this non-TCR-mediated O 2 ·-originates upon stimulation of Fc receptors on monocytes contaminating purified T-cell suspensions Belikov et al, 2014).…”
Section: The Ws Of Ros Production In T Cells: When Where What and Whymentioning
confidence: 79%
“…The importance of the intracellular GSH pool in T-cell activation has been also shown using inhibitors of GSH synthesis, which reduced CD3-mediated proliferation and IL-2 production (Gmunder et al, 1990;Suthanthiran et al, 1990;Smyth, 1991;Hehner et al, 2000). More recently, it has been shown that natural antioxidants such as SOD, catalase, and ascorbate do not have any effects on the proliferation of human primary T cells upon CD3 × CD28 stimulation (Belikov et al, 2014). Thus, after three decades of intense scrutiny, it is still controversial whether ROS support or suppress T-cell functions.…”
Section: T-cell Activation Is Sensitive To Oxidationmentioning
confidence: 98%
See 3 more Smart Citations